DEVELOPMENT OF SHARE FRAMEWORK-BASED LEARNING VIDEO IN IMPROVING CARING ATTITUDE IN STUDENTS - Rahayu, Henik Tri; Herlianita, Risa; Kartika, Annisa Wuri; Dewi, Sofia Rhosma (Asosiasi Institusi Pendidikan Ners Indonesia (AIPNI), 2022)
Introduction: Caring is the core of the nursing process. Caring is the core competency standard that needs to be improved at the educational stage. SHARE framework is a learning strategy that is improved based on the framework to improve patient satisfaction. This study aims to develop a SHARE framework-based learning video to improve nursing students' caring attitudes.Methods: A sequential mixed methods study was used using Focus Group Discussion (FGD) in the first stage and a survey approach in the second stage. Ten nurses with more than ten years of experience caring for patients at the hospital located in Malang participated in FGD and obtained it by purposive sampling. Data collection followed FGD guidelines, and FGD was video recorded, then transcript verbatim for data analysis. Data were analyzed using thematic analysis.Results: Findings suggested five central themes of caring attitude that need to be improved in providing care consist of (1) Sense the patient’s needs, (2) helping the patient out, (3) acknowledging the patient’s feelings, (4) respect patient’s dignity and privacy, and (5) explain what is happening as mentioned in the SHARE Framework. The results of the FGD are included in the video scenario that will be made. The learning videos that have been compiled are then applied to nursing student learning.Conclusion: The development of a caring attitude based on the SHARE framework could be implemented by improving patient comfort through assessment and determination of the right problem, paying attention to the patient’s hygiene, meeting patient needs through creativity and innovation, building trusting relationships with patients and families, be a good listener, respecting patient wishes, use appropriate nonverbal language, greet the patients and provide appropriate education to the patient.